Perspectives on validation in digital soil mapping of continuous attributes—A review - Piikki, Kristin; Wetterlind, Johanna; Söderström, Mats; Stenberg, Bo (Soil use and management, 2021)
We performed a systematic mapping of validation methods used in digital soil mapping (DSM), in order to gain an overview of current practices and make recommendations for future publications on DSM studies. A systematic search and screening procedure, largely following the RepOrting standards for Systematic Evidence Syntheses (ROSES) protocol, was carried out. It yielded a database of 188 peer‐reviewed DSM studies from the past two decades, all written in English and all presenting a raster map of a continuous soil property. Review of the full‐texts showed that most publications (97%) included some type of map validation, while just over one‐third (35%) estimated map uncertainty. Most commonly, a combination of multiple (existing) soil sampe datasets was used and the resulting maps were validated by single data‐splitting or cross‐validation. It was common for essential information to be lacking in method descriptions. This is unfortunate, as lack of information on sampling design (missing in 25% of 188 studies) and sample support (missing in 45% of 188 studies) makes it difficult to interpret what derived validation metrics represent, compromising their usefulness. Therefore, we present a list of method details that should be provided in DSM studies. We also provide a detailed summary of the 28 validation metrics used in published DSM studies, how to interpret the values obtained and whether the metrics can be compared between datasets or soil attributes.